2010
DOI: 10.1093/pch/15.5.295
|View full text |Cite
|
Sign up to set email alerts
|

Invasive group A streptococcal disease: Management and chemoprophylaxis

Abstract: Given the potentially devastating consequences of severe invasive group A streptococcal disease, attention has been directed toward the role of chemoprophylaxis and the optimization of management strategies. In response to this issue, Canadian guidelines were previously developed. However, the uptake of these recommendations is variable across Canada. The present document summarizes key components of the recommendations for use by Canadian physicians. The importance of penicillin in the treatment of group A st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…46 While penicillin is still considered as the first-choice drug for uncomplicated streptococcal infections, they have been proven ineffective in invasive infections. 47 In fact, based on the recommendations of the Infectious Diseases Society of America, penicillin should be used in combination with a protein synthesis inhibitor (eg, clindamycin) in these clinical cases. 48 The use of clindamycin for lifethreatening invasive infections was shown to reduce mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…46 While penicillin is still considered as the first-choice drug for uncomplicated streptococcal infections, they have been proven ineffective in invasive infections. 47 In fact, based on the recommendations of the Infectious Diseases Society of America, penicillin should be used in combination with a protein synthesis inhibitor (eg, clindamycin) in these clinical cases. 48 The use of clindamycin for lifethreatening invasive infections was shown to reduce mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of a therapeutic window of time for treatment of GAS NF is critical ( 8 , 10 , 13 , 15 , 16 ). We showed that treatment of infected mice with ISRIB or GSK2656157 12 hours after infection successfully terminated the infection.…”
Section: Discussionmentioning
confidence: 99%
“…The initial lesion may appear only as mild erythema, but inflammation becomes extensive within a short period, leading to a destructive skin and soft tissue process over large body areas ( 15 ). The mainstay of treatment for invasive GAS diseases is administering antibiotics, surgical debridement of infected tissues, and supportive care ( 16 ). Unfortunately, regardless of prompt therapy, the associated mortality rate from NF remains high, ranging from 23 to 35% in resource-rich settings ( 7 , 8 , 10 , 11 , 13 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, a lincosamide antibiotic (usually clindamycin) and IVIG are generally recommended for the management of severe iGAS disease, albeit with limited evidence in children. [28][29][30] Previous studies suggest that adding clindamycin may reduce mortality. 31 An adult study demonstrated increased survival when IVIG was used for patients with STSS (34% vs. 87% survival rate at 30 days).…”
Section: Discussionmentioning
confidence: 99%